Guidelines for Digital Technology Management for Administration of the Schools under the Office of Khon Kaen Primary Educational Service Area 1 - Piamphuechana, Niyada (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
The objectives of the research article were 1) to study the needs of digital technology management for administration of the schools 2) to study the guidelines for digital technology management for administration of the schools under the office of KhonKaen Primary Educational Service Area 1. The sample group used in research consisted of school administrators and teachers under the office of KhonKaen Primary Educational Service Area 1, with the total number of 337 people. The research instrument was questionnaire. The statistics used for data analysis comprised frequency, percentage, mean, standard deviation and PNI modified index. The research results were found that: 1. The current situation of digital technology management for the administration of schools under the Office of KhonKaen Primary Educational Service Area 1, in overall, it was rated at a moderate level, the desirable condition of digital technology management, in overall, a high level and the needs for digital technology management, in overall, the aspect at the highest level was general administration, followed by personnel management and budget management, the aspect at the lowest level was academic administration. 2. Guidelines for digital technology management for the administration of schools under the Office of KhonKaen Primary Educational Service Area 1 1) On the aspect of general administration, the administrators should manage information storage system about the census of learners continuously. 2) On the aspect of personnel management, the administrators should manage information storage system of personnel in schools to plan the workforce and allocate sufficient personnel. 3) In terms of budget management, the administrators should manage the system of an audit, following up and report on the use and output of the budget in order to assess the efficiency, economy and cost-effectiveness of resource utilization of schools. 4) Regarding academic administration, the administrators should manage information storage system for integrated learning management between online and regular learning by using variety styles of learning.